Groundwater potential zonation by remote sensing and gis techniques and its relation to the groundwater level in the coastal part of the arani and koratalai river basin, southern india (2013)
Groundwater is being pumped extensively from the coastal part of the Arani and Koratalai River Basin, Tamil Nadu, India for irrigation and water supply to the city of Chennai. The objective of this study is to delineate the groundwater potential zones of this area using Remote Sensing (RS) and Geographic Information System (GIS) techniques. Weighted overlay analysis was used to demarcate the ground- water potential zones. Various thematic layers such as geology, geomorphology, soil, lineament density, drainage density, rainfall and landuse maps were prepared. The geological map was prepared using a Geological Survey of India (GSI) district resource map. Indian Remote Sensing System Linear Imaging Self-scanning Sensor III (IRS-1D LISS III) satellite imagery was used to prepare the geomorphology, soil, lineament density, drainage density, and landuse maps. The final groundwater potential map was prepared by assigning appropriate weightage to different thematic maps and adding them to the final groundwater potential map. The derived groundwater potential map was overlaid with the groundwater level and location of well fields for validation. The map prepared will help in systematic and proper development of groundwater resources in this area to meet the growing water requirements of the city of Chennai. ResumenAguas subterráneas se bombean en gran cantidad desde la parte costera en las cuencas de los ríos Arani, en Tamil Nadu, India, para el riego y el aprovisionamiento de agua a la ciudad de Chennai. El objetivo de este estudio es delinear las zonas potenciales de aguas subterráneas en esta área a través de sistemas de Teledeteción (RS) y de Información Geográfica (GIS). Se hizo un análisis sobrepuesto compensado para demarcar las zonas con posibilidad de tener aguas subterráneas. Se prepararon mapas de uso de la tierra con varios elementos temáticos como geología, geomorfología, terreno, densidad de lineamiento, densi- dad de drenaje y precipitación. El mapa geológico fue preparado a partir del Mapa Distrital de Recursos, del Servicio Geológico de la India (GSI). Fueron utilizadas imágenes satelitales Sensing System Linear Imaging Self-scanning Sensor III (IRS-1D LISS III) para definir la geomorfología, terreno, densidad de lineamientos, densidad de drenaje y mapas de uso del terreno. El mapa final de zonas potenciales de aguas subterráneas se preparó con la superposición apropiada de diferentes mapas temáticos sobre los mapas de aguas subterráneas potenciales. Para la validación apropiada, el mapa derivado se solapó con los de niveles de aguas subterráneas y de zonas de pozos. El mapa preparado ayudará en el desarrollo sistemático y apro- piado de las fuentes hídricas subterráneas en esta área que permita abastecer la creciente demanda de agua de la ciudad de Chennai.